Microwave hydrothermal electrodeposition of nickel carbonate hydroxide/cobalt hydroxide film on nickel foam for cement-based structural supercapacitors. (March 2023) - Tu, J.X.; Chen, X.X.; Xiong, X.B.; Chen, Y.; Ma, J.; Cao, H.Y.; Li, A.J.
Abstract: Electroactive electrode materials for cement-based structural supercapacitors suffer from poor interface contacts with ceramic electrolytes and current collectors due to their poor adhesive to the current collectors and severe reactions during cement hydration process, leading to their inferior capacitive performance relative to conventional supercapacitors. Herein, microwave hydrothermal electrodeposition was developed to deposit a robust composite film of Ni2 (CO3 ) (OH)2 /Co(OH)2 as an electroactive electrode material onto nickel foam. Effects of Ni/Co molar ratio of 0.5, 1, 1.5, and 2 on the microstructure and electrochemical properties of the film electrode were investigated in detail. Subsequently, the film electrode with the optimal electrochemical performance was compared with that by hydrothermal deposition with no microwave involvement. The results showed all the resultant films by microwave hydrothermal electrodeposition showed a crooked sheet morphology with a polycrystalline structure containing lots of dislocations. Among them, the film of a Ni/Co molar ratio of 1 presented the optimal capacitive performance (a specific capacity of 632.8 (1.88) C/g(F/cm 2 ) at 1 (2.97) A/g (mA/cm 2 ), a superlong cycling life of 30, 000 cycles at 10 A/g with a capacity retention of 80.4%) and demonstrated better electrochemical and adhesive properties than that prepared by hydrothermal electrodeposition with no microwave involvement. Finally, this optimal film electrode was employed as the cathode, active carbon as the anode and polyacrylic acid (PAA)-KOH-aluminate cement as the structural electrolyte, an hybrid structural supercapacitor device was assembled, and exhibited a compressive strength of as high as 37.2 MPa and a ionic conductivity of 8.2 mS/cm, and deliver excellent electrochemical performance (specific capacitance of 415.31 mF/cm 2 at 0.5 mA/cm 2, and 80.1% capacitance retention of after 8000 cycles at 1 mA/cm 2 ), which is the best capacitive performance among the reported cement-based structural supercapacitors in the form of civil engineering. Our experimental results reveal that microwave hydrothermal electrodeposition could be utilized to fabricate high-performance electrode materials on nickel foam for structural supercapacitors. Graphical abstract: A microwave hydrothermal electrodeposition strategy was developed to deposit a robust composite Ni2 (CO3 ) (OH)2 /Co(OH)2 film onto nickel foam for cement-based structural supercapacitors. Image 1 Highlights: A cement-based structural supercapacitor was proposed for load-bearing application. Robust Ni2 (CO3 ) (OH)2 /Co(OH)2 film was synthesized by microwave hydrothermal electrodeposition. The CSSC device demonstrated a high columbic efficiency close 95% after 8000 cycles.